2022
DOI: 10.1186/s13063-022-06512-5
|View full text |Cite|
|
Sign up to set email alerts
|

Building Emotional Awareness and Mental Health (BEAM): study protocol for a phase III randomized controlled trial of the BEAM app-based program for mothers of children 18–36 months

Abstract: Background The prevalence of maternal depression and anxiety has increased during the COVID-19 pandemic, and pregnant individuals are experiencing concerningly elevated levels of mental health symptoms worldwide. Many individuals may now be at heightened risk of postpartum mental health disorders. There are significant concerns that a cohort of children may be at-risk for impaired self-regulation and mental illness due to elevated exposure to perinatal mental illness. With both an increased pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Using a rapid cycle iteration approach, involving the incorporation of pilot study feedback from both infant and toddler target ages and focus group participant interview content, improvements to the program have been made prior to additional testing. Larger efficacy trials that address the identified challenges and include longer-term follow periods are currently underway [ 93 ]. This will allow us to explore whether there are sustained beneficial effects of the BEAM program.…”
Section: Discussionmentioning
confidence: 99%
“…Using a rapid cycle iteration approach, involving the incorporation of pilot study feedback from both infant and toddler target ages and focus group participant interview content, improvements to the program have been made prior to additional testing. Larger efficacy trials that address the identified challenges and include longer-term follow periods are currently underway [ 93 ]. This will allow us to explore whether there are sustained beneficial effects of the BEAM program.…”
Section: Discussionmentioning
confidence: 99%
“…The program is focused on mental health symptoms, with CBT being consistently found to effectively improve symptoms of depression and anxiety (Komariah et al, 2022), with some evidence showing additional positive effects on parenting-related stress (Ngai et al, 2016). BEAM is a recently developed interactive app-based group therapy and psychoeducational program targeting both mental health and parenting stress through values-based behavioural and self-compassion strategies targeting mental health symptoms combined with emotion-focused parenting strategies (Xie et al, 2022). BEAM is a 10-week program that includes weekly 1-hour group therapy sessions with other parents and clinicians and access to a mobile app that provides weekly educational videos on mental health and parenting skills, a private online forum to connect with other parents, and optional work sheets.…”
Section: Introductionmentioning
confidence: 99%